Activating Critical Thinking Skills through Stand-Up Comedy in the EFL Classroom: A Discourse Analysis of Gabriel Iglesias' "Gabriel Goes to India" - Yusuf Al Arief; Sartika - Hijriati; Ika Susanti; Dian Karina (Jurnal Ilmiah Telaah, 2026)
Critical thinking skills (CTS) are competencies explicitly prioritized in Indonesian higher education. However, EFL classrooms generally lack evidence-based approaches to developing these skills through authentic materials. Previous studies have documented the affective benefits of humor in language teaching (Arief, 2023; Saito et al., 2025) and established that humor processing involves cognitive operations such as incongruity detection and stereotype evaluation (Attardo, 2020; Tsakona, 2020a). However, no study has systematically mapped the discourse features of stand-up comedy texts to CTS components for the benefit of EFL pedagogy. This study fills this gap by analyzing Gabriel Iglesias' stand-up comedy special "Gabriel Goes to India" using Facione's (1990) CTS taxonomy. Using qualitative discourse analysis guided by Attardo's (2020) General Theory of Verbal Humor, this study identified five categories of discourse features in the transcripts: cultural stereotyping, incongruity and script opposition, subversive humor, intertextual references, and cross-cultural meta-commentary. Each category activated specific components of CTS: cultural stereotyping activated evaluation; incongruity activated analysis and inference; subversive humor activated interpretation; intertextuality required a shift from cultural literacy to critical literacy; and cross-cultural reflection activated self-regulation. Based on these findings, this study proposes a pedagogical framework that maps these discourse features to CTS components, along with suggested classroom activities for the Indonesian EFL context.